Ketal Sugar Conversion Into Green Hydrocarbons by Faujasite Zeolite in a Typical Catalytic Cracking Process - Pinto, Joana; Pedrosa, Igor; Linhares, Camila; San Gil, Rosane A. S.; Lam, Yiu Lau; Pereira, Marcelo Maciel (Frontiers in Chemistry, 2019)
Fluidized catalytic cracking (FCC) converts hydrocarbons in the presence of a catalyst based on faujasite zeolite (USY and REY). While hydrocarbon is poorly reactive, biomass and its derived compounds are highly functionalized and not suitable to a typical FCC process. To overcome this limitation biomass was first converted into a dense and stable bio-crude composed mainly of ketal-sugar derivatives by using acetone in diluted acid. Here, a representative compound of this bio-crude, 1,2:3,5-di-O-isopropylidene-α-D-xylofuranose (DX) in n-hexane, was converted by USY and a commercial FCC catalyst containing USY, at 500°C, in a fixed bed and fluidized bed reactors, respectively. Faujasite Y is very efficient in converting DX. More than 95% conversion was observed in all tests. Over 60 wt.% was liquid products, followed by gas products and only around 10% or less in coke. The higher the catalyst activity the greater the aromatics in the liquid products and yet higher coke yields were observed. In particular, simulating more practical application conditions: using deactivated catalyst in a fluidized bed reactor, improved green hydrocarbons production (mono-aromatic up to 10 carbons and light hydrocarbon up to eight carbons) and unprecedented lower coke yield (≈5 wt.%) for bio-feeds. The present results further suggest that catalyst will play a primary role to convert the bio-crude into target hydrocarbons and overcome the transition of a non-renewable to a renewable refinery feed.